A photo-stable and electrochemically stable poly(dumbbell-shaped molecules) for blue electrophosphorescent host materials. Issue 6 (5th November 2014) - Li, Lu; Hu, Tian-Qing; Yin, Cheng-Rong; Xie, Ling-Hai; Yang, Yang; Wang, Chao; Lin, Jin-Yi; Yi, Ming-Dong; Ye, Shang-Hui; Huang, Wei
Abstract : Hindrance functionalization at the reactive sites makes π-stacked polymers highly stable with the potential applications related to organic electronic devices. Abstract : Hindrance functionalization at the reactive sites makes π-stacked polymers highly stable for applications related to organic electroluminescent devices. Herein, a novel stable polymer host material, poly(3, 6-bis(9-phenylfluoren-9-yl)-9-vinyl-carbazole) (PVKDPF), has been designed and synthesized from dumbbell-shaped monomers by introducing two bulky 9-phenylfluorenyl moieties (PFMs) to the carbazole units. PVKDPF, with a high triplet energy level of 2.85 eV, shows outstanding thermal and morphological stability. Interestingly, as compared to its precursor, poly( N -vinylcarbazole) (PVK), PFMs-capped PVKDPF shows enhanced anti-photoaging against UV light, along with a much better electrochemical stability, without any obvious change even after repeated scanning during cyclic voltammetry. The prototype blue phosphorescent polymer light-emitting devices (PhPLEDs) using PVKDPF as the host and doped with the FIrpic guest exhibit excellent blue electroluminescence with the Commission Internationale de L'Eclairage (CIE) coordinate of (0.184, 0.381), luminous efficiency corresponding to 17.3 cd A −1, and power efficiency corresponding to 9.0 lm W −1 . Hindrance-capped dumbbell-shaped polymers are robust polymer semiconductors that can be used in mechatronic devices.